2014
DOI: 10.1016/j.jsbmb.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal domain of the androgen receptor drives its nuclear localization in castration-resistant prostate cancer cells

Abstract: Androgen-independent nuclear localization is required for androgen receptor (AR) transactivation in castration-resistant prostate cancer (CRPC) and should be a key step leading to castration resistance. However, mechanism(s) leading to androgen-independent AR nuclear localization are poorly understood. Since the N-terminal domain (NTD) of AR plays a role in transactivation under androgen-depleted conditions, we investigated the role of NTD in AR nuclear localization in CRPC. Deletion mutagenesis was used to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…The expression vector pEGFP-C1 (Clontech, Mountain View, CA) was used to generate fusion protein constructs with GFP at the N terminus of AR and the NAR mutant for convenient visualization using fluorescent microscopy as described earlier (21). PSA promoter-driven luciferase reporter vector (pPSA6.1) was kindly provided by Dr. Marianne Sadar and a tk promoter-driven Renilla luciferase reporter (pRL-TK) was purchased from Promega (Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…The expression vector pEGFP-C1 (Clontech, Mountain View, CA) was used to generate fusion protein constructs with GFP at the N terminus of AR and the NAR mutant for convenient visualization using fluorescent microscopy as described earlier (21). PSA promoter-driven luciferase reporter vector (pPSA6.1) was kindly provided by Dr. Marianne Sadar and a tk promoter-driven Renilla luciferase reporter (pRL-TK) was purchased from Promega (Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…These observations suggested that Hsp70 binds to AR through NTD AR , with the a.a. 294–556 being the most important region for the binding. We have previously shown that region a.a. 294–556 is required for androgen-independent AR nuclear localization in CRPC cells (35). The binding of Hsp70 to this region of AR may suggest a role for Hsp70 in promoting androgen-independent AR nuclear localization in CRPC cells, however further studies will be required to fully elucidate the significance of Hsp70 binding to the C-terminal portion (a.a. 294–556) of NTD AR .…”
Section: Resultsmentioning
confidence: 99%
“…Human AR and its deletion mutants, amino acid 1–560 (N-terminal domain, NTD), 1–665 (NAR), 558–920 (DNA Binding domain, Hinge region and ligand-binding domain, DBDH-LBD), 668–920 (ligand-binding domain, LBD) coding sequence, were inserted separately into pEGFP-C1 vector, generating GFP-AR, GFP-NTD AR , GFP-NAR, GFP-DBDH-LBD AR , and GFP-LBD AR , GFP-AR a.a.1−293 and GFP-AR a.a.294−556 plasmids (35). Hsc70, Hsp70 and its Nucleotide Binding domain (NBD a.a. 1–386), and Substrate Binding domain (SBD a.a. 386–641) coding sequence were inserted into pCMV-3Tag-1A vector to make Flag-Hsc70, Flag-Hsp70, Flag-NBD and Flag-SBD plasmids.…”
Section: Methodsmentioning
confidence: 99%
“… 30 It has also been suggested that expression of the NTD may drive androgen independent nuclear localization and suppress nuclear export of the AR in CRPC. 31 …”
Section: The Role Of the Ar-ntd In Receptor Functionmentioning
confidence: 99%